Marco teórico jurídico del derecho de admisión en el Ecuador - Ríos Almeida, Freddy Andrés (2010)
This work is a consequence of a personal experience, after a detailed analysis of the legal concepts involved in this situation, which shows the existence of an “admission right”, not as the owner power for discrimination, but like a relational human right, which is recognized and warranted by the Ecuadorian Constitution of 2008. A time and space retrospective analysis has been done, regarding the bases of the human rights, that will later be called liberty rights and social rights, currently recognized in our Constitution. A Legally protected interest of the admission right has been decipher by an analysis, and how it´s configure as a human right.